Population diversification in geographically varied population of Lonchura punctulata in India based on 12SrRNA and morphometry - Atul Kathait; Devinder Kumar Sharma; P Narashimha Reddy; Ajay Gaur; Asha Chandola- Saklani (World Journal of Experimental Biosciences, 2016)
Morphological characters of birds imitate their adaption occurred due to evolution and pressure of environmental for their ecological requirements. These characters are also significant towards their phylogenetic relationships in a genus and family. Lonchura genus is represented by colorful passerine birds widely distributed in Asia, Africa and Australia. One of their member Spotted munia is widely distributed in India in same type of habitat with similar kind of morphological appearances. However the populations show great variability in their physiology according to their altitudinal distributions. In the present study investigations were made to find the genetic and morphometric variation in the geographically varied population of spotted munia in India. Wild birds were caught, samples and data were collected for genetic and morphometric comparison. Data were analysed statistically and comparisons were made at population levels. In morphometric comparison we observed that the lengths northern population (101.8 mm) is high as compared to southern population (96.5 mm). We significantly observed the differences in other parameters too. In genetic comparisons separate population clusters were seen according to geographical locations. We observed morphometric variation according to their altitude. Higher altitude populations are big in size in compare to lower altitude population. It might be due to environmental pressure on their flight, food, prey and breeding. Similar differences were seen in genetic parameters too. Northern populations were seemed to be more genetically varied in compare to southern populations, indicate the ongoing process of speciation.
Keywords: 12S r RNA, Altitude, Haplotype, Morphometric, Phylogeography, Spotted Munia.